Behind the Gun of Densus 88: Understanding U.S. Government Behavior under Crisis Situation - Arif, Muhammad Qobidl Ainul (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2015)
Before 9/11 attack, U.S. and Indonesia military relation was under the shade of confrontation rather than cooperation since the imposing of U.S. embargo on military training and weaponry transfer after Santa Cruz tragedy in 1991. However, throughout 2003 and 2004, when Indonesia was still in the embargo, U.S. government reportedly supported the establishment of an elite force in Indonesia named Special Detachment 88 Anti-Terror which also known as Densus 88. 9/11 attack and many terrorism activities throughout the world in its aftermath were situating U.S. government under crisis situation. Based on existed evidences, the author concludes that under crisis situation, U.S. government is highly possible violating its own foreign policy line as indicated with its support to Densus 88 in Indonesia.